PEMBANGUNAN RORAK DAN APLIKASI TANKOS DI AREAL PERKEBUNAN KARET (THE STUDY OF SILT PITS ESTABLISHMENT AND EMPTY FRUIT BUNCH APPLICATION IN RUBBER PLANTATION) - Priyo Adi Nugroho (Inovasi, 2017)
Rubber tree (Hevea brasiliensis) is almost widely distributed throughout Indonesia which has varieties in soil and climate. Hence the modifications of rubber cultivation technique occur for adapting to the varieties of location. In low rainfall area water conservation become important to meet the plant water requirement during the dry season. Otherwise in high rainfall and hilly area, soil conservation is the main focus in order to reduce the declining of soil fertility. Silt pit or infiltration pit is a common conservation practice in perennial crop plantation area in Indonesia. Several studies reported that silt pit improved soil water capacity and delayed soil dryness for 3.5 months. Silt pit shortened the length of slope thus, the surface run-off decreased until 23.3% which in turn the depletion potency of land quality by soil degradation could be avoided. The effectivity of fertilizer that is applied on pit becomes more efficient so that give the positive impact on girth increment and rubber yield. In order to optimize the effect for the tree, silt pit can be combined with plantation waste i.e. empty fruit bunch (EFB). Numerous researchers said that EFB recommended to be applied in plantation area due to its advantage on improving the soil characteristics and raising the rubber root volume. Whether both silt pit and EFB application will be established in rubber plantation, EFB can be placed on pit bed (1-2 layer), with a notification that silt pit size should be deepened. Technically the more of number of pits the better (>150 pits/ha) for run-off and soil erosion reduction. However, it will be better if the number of pits that will be established considering the planter’s financial and the situation of specific location. The role of related technical bureau, extension officer, research institute and university is also necessary for getting the best result. Keywords: Hevea brasiliensis, infiltration pits, empty fruit bunch, erosion